2019
DOI: 10.1080/02670836.2019.1591027
|View full text |Cite
|
Sign up to set email alerts
|

General description of martensite transformation curves – a case for bainite

Abstract: This work describes the results of validation trials of a formal model for the martensite transformation curve in steels. The model is based on microstructural evolution and accepted aspects of athermal, isothermal, mechanical-induced as well as magnetic-assisted martensite transformation modes. The model is operational for martensite and applicable to other intragrain transformations. The paper also explores the extension of the formalism to bainite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…In previous work [5][6][7] , ξ was equal to temperature, magnetic field, mechanical deformation, and of course time. In this paper, one uses ξ = t. That is, this paper considers only isothermal kinetics.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work [5][6][7] , ξ was equal to temperature, magnetic field, mechanical deformation, and of course time. In this paper, one uses ξ = t. That is, this paper considers only isothermal kinetics.…”
Section: Theorymentioning
confidence: 99%
“…Nonetheless, in many transformations, one observes that there is an incubation time. The proposed alternative to Avrami's equation was introduced to describe martensitic transformations [5][6][7] . Subsequent work suggested that the equation could describe bainitic transformations 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing the transformations in steels, the present authors have proposed an alternative to Avrami's equation [9][10][11]…”
Section: Introductionmentioning
confidence: 99%
“…In the equation above, x is an "advance" variable, which in previous works [9][10][11] was equal to temperature, magnetic field, mechanical deformation, and time. The x i is the first datum in a dataset.…”
Section: Introductionmentioning
confidence: 99%